2013
DOI: 10.1111/anu.12022
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different dietary lipid levels on the reproduction ofRhamdia quelen(Quoy and Gaimard, 1824)

Abstract: Lipids include some of the most important nutrients that affect the survival and growth of fishes in their early life stages. Lipid deficiency prior to spawning may significantly reduce egg production, hatchability and the number of surviving larvae. In this study, we investigated the effects of isocaloric diets containing 80, 140 and 200 g kg À1 of lipids (lipid source, soy oil) for 90 days. The following data were collected at 0, 45 and 90 days: final weight; length; conditioning factor; hepatosomatic, gonad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
2
6
2
2
Order By: Relevance
“…Sargent et al (2002) observed greater conversion for n-3 production, especially DHA, than for n-6 in ovary and oocyte. This is in agreement with Coldebella et al (2013) and corroborates the potential for fatty acids to be mobilized from the tissues to the oocytes (Tocher, 2003).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Sargent et al (2002) observed greater conversion for n-3 production, especially DHA, than for n-6 in ovary and oocyte. This is in agreement with Coldebella et al (2013) and corroborates the potential for fatty acids to be mobilized from the tissues to the oocytes (Tocher, 2003).…”
Section: Discussionsupporting
confidence: 86%
“…Few studies (Coldebella et al, 2013) focusing on fatty acids profiles of ovaries and eggs of R. quelen have been conducted using soybean oil at different levels of inclusion. The present study compared the effects of diets based on fish oil and those supplemented with soybean or palm lipids, alone and in combination with fish oil, on the growth, reproductive performance, and the fatty acid composition of ovaries and oocytes in South American catfish in their first reproductive cycle.…”
Section: Introductionmentioning
confidence: 99%
“…The effects observed for GSI and HSI corroborate the results reported by Bombardelli et al (2009), who worked with different energy levels in the diets of female Nile tilapia and also found that there were no significant effects of diet on these parameters. Coldebella et al (2013) evaluated different levels of soil oil for female catfish (Rhamdia quelen) and also observed no differences between treatments for the same variables; however, females fed diets with 140 and 200 g/kg lipids displayed greater accumulations of visceral fat. In contrast to these results, Oliveira et al (2014) observed an inverse relationship between hepatosomatic and gonadosomatic indices with a 380 g/kg crude protein level in the diet of adult female Nile Tilapia, with an initial average weight of 764 g. Table 5 -Body composition (% of dry matter) of broodstock fed diets with different digestible energy levels (mean±SEM)…”
Section: Discussionmentioning
confidence: 93%
“…The gonadosomatic index suffers little influence from dietary components like lipids (Coldebella et al, 2013) or energy content (Tessaro et al, 2014). In silver catfish, the gonadosomatic index is strongly influenced by seasonality and, in both sexes, the gonadosomatic peak coincides with testosterone peak (Barcellos et al, 2002).…”
Section: Discussionmentioning
confidence: 99%